2008
DOI: 10.1128/iai.00156-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of Porphyromonas gingivalis SerB in Gingival Epithelial Cell Cytoskeletal Remodeling and Cytokine Production

Abstract: The SerB protein of Porphyromonas gingivalis is a HAD family serine phosphatase that plays a critical role in entry and survival of the organism in gingival epithelial cells. SerB is secreted by P. gingivalis upon contact with epithelial cells. Here it is shown by microarray analysis that SerB impacts the transcriptional profile of gingival epithelial cells, with pathways involving the actin cytoskeleton and cytokine production among those significantly overpopulated with differentially regulated genes. Consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 60 publications
0
76
0
3
Order By: Relevance
“…This experiment indicated that MtSerB2 acted in a similar capacity as SerB653 from Porphyromonas gingivalis (P. gingivalis), previously shown to induce microtubule rearrangement in HIGK cells (human immortalized gingival Fig. 1 continued keratinocytes) [35,37,38]. Recently, the same group published a follow-up study and showed that MtSerB2 was secreted in the cytoplasm of infected THP1 macrophages [30].…”
Section: Serb2mentioning
confidence: 66%
“…This experiment indicated that MtSerB2 acted in a similar capacity as SerB653 from Porphyromonas gingivalis (P. gingivalis), previously shown to induce microtubule rearrangement in HIGK cells (human immortalized gingival Fig. 1 continued keratinocytes) [35,37,38]. Recently, the same group published a follow-up study and showed that MtSerB2 was secreted in the cytoplasm of infected THP1 macrophages [30].…”
Section: Serb2mentioning
confidence: 66%
“…It was proposed that this could facilitate survival and multiplication of the entire microbial community [59]. P. gingivalis can block gingival epithelial cells IL-8 production in vitro, by secreting a serine phosphatase that inhibits the synthesis of IL-8 [60]. This process can delay the recruitment of neutrophils preventing the proper formation of the neutrophil wall, facilitating initial microbial colonization of the periodontium [61].…”
Section: Host Defense Mechanismsmentioning
confidence: 99%
“…Clients generally find it easier to identify the cognitive distortions and biased thinking of others and then apply the skill to their own cognitions, with group members frequently filling the role of co-therapists [24]. The group setting also provides an opportunity for modelling the desired behaviours by group facilitators and members by displaying empathy, support and encouragement, as well as promoting change via challenging negative automatic thoughts and distorted cognitions.…”
Section: Introductionmentioning
confidence: 99%